The Nexus of Sharia Financial Literacy, Inclusion, and Technology with SME Performance: A Study in East Java - Arzety, Happy Miranda; Sukmaningrum, Puji Sucia (EQUILIBRIUM, 2024)
SMEs are a business sector with an important role in the economy with significant contributions to Gross Domestic Product (GDP) and job creation, including in East Java Province as one of the provinces with the 3rd largest number of SMEs in Indonesia. However, the increase of SMEs in Indonesia requires SMEs to survive in a very tight competition. In surviving the competition, the main challenges faced by SMEs to improve their innovation and performance include access to financial resources, ineffective understanding and management of financial management, and utilization of financial products and services. Therefore, the purpose of this study is to analyze the effect of Islamic financial literacy, financial inclusion and sharia financial technology on the performance of SMEs in East Java. This study uses a quantitative approach with a sample of 100 people. The analysis technique used is SEM-PLS. The results of study indicate that the performance of SMEs in East Java has a significant effect on Islamic financial literacy, financial inclusion, and sharia financial technology. In addition, there is also mediating effect of financial inclusion on Islamic financial literacy and sharia financial technology on the performances of SMEs in East Java. With this research, it is expected that there will be more education and training programs on Islamic financial literacy, create policies that can encourage financial inclusion and innovate sharia financial technology products adapted to the needs of SMEs through collaboration between the government, Islamic financial institutions, and the community.